Rationale for bone marrow transplantation in the treatment of autoimmune diseases. - Ikehara, S (1985)
Transplantation of normal bone marrow from C3H/HeN nu/nu (H-2k) mice into young MRL/MP-lpr/lpr (MRL/l; H-2k) mice (less than 1.5 mo) prevented the development of autoimmune diseases and characteristic thymic abnormalities in the recipient mice. When female MRL/1 (greater than 2 mo) or male BXSB (H-2b) mice (9 mo) with autoimmune diseases and lymphadenopathy were lethally irradiated and then reconstituted with allogeneic bone marrow cells from young BALB/c nu/nu (H-2d) mice (less than 2 mo), the recipients survived for more than 3 mo after the bone marrow transplantation and showed no graft-versus-host reaction. Histopathological study revealed that lymphadenopathy disappeared and that all evidence of autoimmune disease either was prevented from developing or was completely corrected even after its development in such mice. All abnormal T-cell functions were restored to normal. The newly developed T cells were found to be tolerant of both bone marrow donor-type (BALB/c) and host-type (MRL/1 or BXSB) major histocompatibility complex (MHC) determinants. Therefore, T-cell dysfunction in autoimmune-prone mice can be associated with both the involutionary changes that occur in the thymus of the autoimmune-prone mice and also to abnormalities that reside in the stem cells. However, normal stem cells from BALB/c nu/nu donors can differentiate into normal functional T cells even in mice whose thymus had undergone considerable involution, as in the case of BXSB or MRL/1 mice in the present studies. These findings suggest that marrow transplantation may be a strategy ultimately to be considered as an approach to treatment of life-threatening autoimmune diseases in humans. T-cell dysfunction in autoimmune-prone mice previously attributed to involutionary changes that occur in the thymus of these mice may instead be attributed to abnormalities that basically reside in the stem cells of the autoimmune-prone mice.